2005
DOI: 10.1002/csr.93
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to certified timber and paper uptake in the construction and paper industries in the United Kingdom

Abstract: Whilst forest management certification emerged in the early 1990s as a potential market-based solution to the problem of forest loss and degradation, certified timber has not yet taken a significant share of timber and wood product markets. Although the lack of supply of certified timber is acknowledged as a problem, market barriers to the uptake of certified products are poorly understood. This study sought to identify and compare barriers to the uptake of certified wood and wood products in the UK's paper an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The market situation for certified wood products has steadily improved during the 2000s, but with occasional exceptions in the case of tropical hardwoods in the European market, achievable price premiums tend to remain negligible (UNECE/FAO2009). Three types of barriers have been identified by Werndle et al (2006) as the major constraints on certified timber and paper product uptake; first, supply barriers, which include lack of certified timber available, supply chain complexities, entrenched supplier relationships, and a currently low or non-existent price premium on certified forest products; second, demand barriers, which include lack of certification knowledge on the part of final consumers, price sensitivity, weak market demand; and third, organizational barriers, which include lack of strategic commitment, inadequate management systems, staff skills and financial provision. Since industrial consumers form the main customer base in the forest industry, Werndle et al (2006) suggested that educating subcontractors about certification and tightening control over procurement by large contractors could be one solution on the demand side.…”
Section: Discussion and Generation Of Hypotheses For Further Researchmentioning
confidence: 99%
“…The market situation for certified wood products has steadily improved during the 2000s, but with occasional exceptions in the case of tropical hardwoods in the European market, achievable price premiums tend to remain negligible (UNECE/FAO2009). Three types of barriers have been identified by Werndle et al (2006) as the major constraints on certified timber and paper product uptake; first, supply barriers, which include lack of certified timber available, supply chain complexities, entrenched supplier relationships, and a currently low or non-existent price premium on certified forest products; second, demand barriers, which include lack of certification knowledge on the part of final consumers, price sensitivity, weak market demand; and third, organizational barriers, which include lack of strategic commitment, inadequate management systems, staff skills and financial provision. Since industrial consumers form the main customer base in the forest industry, Werndle et al (2006) suggested that educating subcontractors about certification and tightening control over procurement by large contractors could be one solution on the demand side.…”
Section: Discussion and Generation Of Hypotheses For Further Researchmentioning
confidence: 99%
“…From a value-added perspective, a societal strategy of universal certification of forests with no certification-related price distinction between products would be vastly different from selective certification of forests leading to price differentiation between certified and noncertified products. In any event, the former is currently precluded by widespread unsustainable forestry practices in many parts of the world, and the latter is subject to a host of market barriers (Werndle et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, it has taken various initiatives in many countries (van Kooten, Nelson, & Vertinsky, 2005;Werndle, Brown, & Packer, 2006), among which the Netherlands. FSC-International is a multistakeholder initiative founded in 1993, with the ambition to improve sustainable forestry worldwide through certification.…”
Section: Fsc-nl: Convener Of the Csspmentioning
confidence: 99%
“…FSC-International is a multistakeholder initiative founded in 1993, with the ambition to improve sustainable forestry worldwide through certification. To this end, it has taken various initiatives in many countries (van Kooten, Nelson, & Vertinsky, 2005;Werndle, Brown, & Packer, 2006), among which the Netherlands. FSC-NL is not a standard-setting organization (as FSC-International) but manages the FSC-standard for Dutch forests and supervises FSC certification in the Netherlands.…”
Section: Fsc-nl: Convener Of the Csspmentioning
confidence: 99%